2022
DOI: 10.1108/sajbs-06-2021-0239
|View full text |Cite
|
Sign up to set email alerts
|

Information technology investment and working capital management efficiency: evidence from India survey data

Abstract: PurposeThis study aims to test the relationship between information technology investment (IT_INVEST) and working capital management (WCM) efficiency.Design/methodology/approachThis study utilized a survey research design to collect data from micro, small and medium enterprises (MSMEs) owners in India.FindingsEmpirical results show that perceived IT_INVEST plays a role in improving WCM efficiency by decreasing the inventory holding period and reducing the cash conversion cycle (CCC) in India. A three-stage lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Meanwhile, a positive significant relationship between efficiency and profitability is justifiable as assets turnover and both ratios ROA and ROE measure company efficiency. Similar positive significant relationship is found for WC, as linkage between operational efficiency and WC was justified by several studies (Gill et al , 2022). Firms with high volatility of operational results particularly young SMEs have lower probability of survival, whereas old SMEs’ high volatility could contribute positively to company’s performance.…”
Section: Discussionsupporting
confidence: 80%
“…Meanwhile, a positive significant relationship between efficiency and profitability is justifiable as assets turnover and both ratios ROA and ROE measure company efficiency. Similar positive significant relationship is found for WC, as linkage between operational efficiency and WC was justified by several studies (Gill et al , 2022). Firms with high volatility of operational results particularly young SMEs have lower probability of survival, whereas old SMEs’ high volatility could contribute positively to company’s performance.…”
Section: Discussionsupporting
confidence: 80%
“…Advanced IT capabilities also make it easier for supply chain partners to coordinate among themselves (Banker et al, 2006; Dehning et al, 2007; Gelsomino et al, 2016). A recent study, by Gill et al (2022), showed that IT investment improves working capital management by decreasing inventory holding periods and cash conversion cycles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research finds that countries with safer legal systems and better investor protection have more efficient working capital (Mättö and Niskanen, 2020). In addition, Gill et al (2022) show that IT investment reduces the inventory holding period and the cash conversion cycle (CCC), and, thereby, improving WCM efficiency.…”
Section: Introductionmentioning
confidence: 99%